THE GREAT SCHOLARS OF IX-XII CENTURIES IN MOVAROUNNAHR AND KHURASAN ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the great scholars of the 9th to 12th centuries in Movarounnahr and Khurasan, two historically significant regions of Central Asia and Persia. It provides an overview of Movarounnahr and Khurasan, highlighting their cultural and intellectual significance during this period. The article then delves into the achievements and contributions of prominent scholars who emerged from these regions, focusing on their advancements in various fields such as philosophy, science, literature, and Islamic scholarship. Through an examination of their works and influence, this article sheds light on the rich intellectual heritage of Movarounnahr and Khurasan during the medieval period.